The Analysis of Biology Learning Assesment Implementation in Jepara High School During Covid-19 Pandemic - Rohman, Alif Khoirur; Widiyaningrum, Priyantini; WH, Nugrahaningsih (Journal of Innovative Science Education, 2022)
The Covid-19 pandemic has changed education that was previously conducted face-to-face to online learning. However, it is still necessary to conduct a learning assessment to determine student learning achievement. This study aims to describe the application of assessment in Biology learning in 3 public high schools in Jepara Regency. This research is a descriptive research with a qualitative approach. Data were taken by means of document analysis, observation and interviews. Data were analyzed using the Milles & Huberman model which consisted of data reduction, data presentation and conclusion drawing. The results of this study indicate that the biology teachers of SMAN 1 Mayong, SMAN 1 Pecangaan and SMAN 1 Welahan have compiled a complete lesson plan and online learning assessment instrument. Assessment techniques used in online learning vary from multiple choice, essay questions, simple practicum, independent projects and portfolios. While the online assessment applications used by teachers include google form, quizizz, google classroom, microsoft teams. The teacher begins learning by providing material to be explained to students, but when a more specific explanation is needed, the teacher usually uses the help of a learning video or video conference using the Zoom Meeting application or Google Meet. Cognitive, affective and psychomotor assessments can be carried out by teachers in online learning.